Let's talk about faces: Identifying faces from verbal descriptions. (4th November 2022) - Tyler, Rebecca; Towler, Alice; Kemp, Richard I.; White, David
Abstract: Face descriptions inform real‐world identification decisions, for example when eyewitnesses describe criminal perpetrators. However, it is unclear how effective face descriptions are for identification. Here, we examined the accuracy of face identification from verbal descriptions, and how individual differences in face perception relate to producing and using descriptions for identification. In Study 1, participants completed a face communication task in pairs. Each participant saw a single face, and via verbal communication only, the pair decided if they were viewing the same person or different people. Dyads achieved 72% accuracy, compared to 81% when participants completed the task individually by matching face pairs side‐by‐side. Performance on the face communication and perceptual matching tasks were uncorrelated, perhaps due to low measurement reliability of the face communication task. In subsequent studies, we examined the abilities of face 'describers' (Study 2) and 'identifiers' separately (Study 3). We found that 'super‐recognizers' – people with extremely high perceptual face identification abilities – outperformed controls in both studies. Overall, these results show that people can successfully describe faces for identification. Preliminary evidence suggests that this ability – and the ability use facial descriptions for identification – has some association with perceptual face identification skill.